Stable transfection of CHO cells with the c-myc gene results in increased proliferation rates, reduces serum dependency, and induces anchorage independence - Ifandi, Vasiliki (Kluwer Academic Publishers, 2003)
Induction of the transcription factor Myc promotes cell proliferation and transformation by activating growth-promoting genes and/or by transcriptionally repressing the expression of growth arrest genes. However, a number of studies have shown that c-Myc is a potent inducer of apoptosis in the absence of serum or growth factors. To further examine the role of Myc in cell growth and proliferation, and the advantages of this positive regulator in cell culture we transfected the CHO-K1 cell line with a human c-myc gene driven by MMLV 5′-LTR promoter. Over-expression of ectopic c-Myc resulted in a significant increase in growth rate and maximum cell number, in both suspension and attached batch culture accompanied by a similar decrease in specific glucose consumption rate. Interestingly, there was no manifestation of the widely reported apoptotic death by c-myc in the absence of serum. Additionally, over-expression of c-Myc appeared to induce morphological transformation and partial anchorage-independence.